Nano Entrepreneurship and Saving-Based Finance Concept in Waqf Literature: A Systematic Review and Future Research Direction - Jahangir, Rashed; Bulut, Mehmet; Bulut, Mehmet (Springer Nature, 2024)
The application of waqf has gradually expanded globally by contributing to various socioeconomic domains, including entrepreneurship, business, housing, poverty alleviation, and funding, along with its core objective—i.e., to ensure social well-being. Numerous studies were conducted, suggesting different solutions to address problems and ameliorate the infrastructure of societies. This study aims to ascertain the frequency of nano entrepreneurship or business and SBF concepts in waqf-related literature. We investigate the number of waqf-centric models toward business or entrepreneurship through the PRISMA-compliant systematic literature review from 2000 to 2022. Using this approach, academic databases are accessed to retrieve the expected sample data, e.g., Scopus, Web of Science, and Taylor & Frances. After analyzing the selected articles, the study reveals that most of the published papers are Malaysia-centric and indexed by the Web of Science database; besides, the highest number of papers were published in 2021, and the “survey” was the most frequently used method for data collection during the sample period. In a nutshell, the results indicate an upward annual trend in entrepreneurship research and other closely linked topics in the waqf sphere. It is worth mentioning that no study related to the concept of nano entrepreneurship and SBF is ascertained through this research. This is the first attempt to search the use of the nano entrepreneurship concept in waqf literature through the PRISMA-compliant systematic literature review.
Islamic Financial Institutions from the Early Modern Period to the 20th Century Comparative Perspectives on the History and Development of Cash Waqfs / Editors:Mehmet Bulut, Bora Altay, Cem Korkut -- Springer Nature -- ISBN:978-303151318-3, 978-303151317-6 -- 2024.